THE MELDING OF ART AND MUSIC IN MEDIA: THE ROLE OF EDUCATION THROUGH ART AND MUSIC - Mathew, Milan; Lakshmi, Aiswarya (International Journal of Research -GRANTHAALAYAH, 2025)
The combination of visual arts and music in media creates a rich experience that advances cognitive and affective involvement. The paper discusses emotional synesthesia, which is a condition in which various sensory modalities—like sight and sound—cross over to create increased emotional reactions. Analyzing the works of Van Gogh, the research takes into account how his vibrant color palette, expressive brushstrokes, and emotionally charged composition connect with musical aspects in order to provide a sublime sensual experience. The current research also examines multimedia case studies such as Van Gogh Alive, Studio Ghibli animation, and experiential AR/VR-based exhibitions to explore how the integration of art and music in media maximizes emotional perception, induces empathy, and improves social awareness. Employing multimodal learning theory and aesthetic engagement theory, the research illustrates how multimedia art promotes SDG 4 (Quality Education) by developing emotional and cultural literacy and SDG 17 (Partnerships for the Goals) by encouraging cross-disciplinary cooperation between media, education, and the arts. The qualitative and theoretical research utilizes art theory, psychology, and media studies to establish the place of multimedia experience in developing international educational policy. The results indicate that immersive media not only intensifies audience involvement but also has a transformative impact on emotional education and cross-disciplinary learning.